Women's Jewelry set of the Northern Altai population in Pre-Turkic period (based on materials of the Choburak-I necropolis) - Seregin Nikolai N.; Matrenin Sergey S. (Поволжская археология)
The article presents the results of an interdisciplinary study of the jewelry collection, discovered during excavations of the pre-Turkic period necropolis at the Choburak-I site. This burial ground, fully excavated by the archaeological expedition of the Altai State University, is located in the Chemal district of the Altai Republic. Decorations, found in three female burials (barrows No. 32a, 33, 34), are represented by the following items: metal earrings (5 copies), large (2 copies) and small (12 copies) sewn-on plates, plaques of various designs and shapes (7 copies), headdress (1 copy), iron (1 copy) and bone (3 copies) pendants. It has been established that these objects have a significant number of analogies in the sites of the Great Migration period, studied in Altai and adjacent territories. At the same time, certain types of earrings and sewn-on plates determine the dating of the Choburak-I necropolis by the time no earlier than the middle of the IV century AD. Based on location of metal artifacts in the burial of barrow No. 34, the possibility of women using two headdresses is substantiated – a frontlet (“diadem”) with a plaque and a cape with a fabric base. It was concluded that the variability of the composition of jewelry in the burials was determined by the different lifetime status of the deceased. The study of the mutual occurrence of decorative elements of headdresses and outer-clothes with other categories of accompaniments to a burial made it possible to assume that the woman buried in barrow No. 34 was a member of the local elite of the Northern Altai nomads of the pre-Turkic period.